Behavioral, social, and emotional well-being in children who stutter: the influence of race-ethnicity. (2nd October 2021) - Briley, Patrick M.; Ellis, Charles
Abstract: Purpose: The purpose of this study was to determine if reports of behavioral, emotional and social well-being in children who stutter differ across racial-ethnic groups. Materials and methods: Using 2010–2015 National Health Interview Surveys, data was analyzed from responses of children who stutter's parents, in the United States, to items of the Strength and Difficulties Questionnaire. Parent responses of reporting Strengths and Difficulties Questionnaire items were determined using multiple logistic regression analyses. Results: This sample included a total 42, 962 children, of which 875 were identified as children who stutter. Among the children who stutter, reports of well-being were compared from 294 non-Hispanic White, 249 non-Hispanic Black, and 332 Hispanic children who stutter. Results indicated Black children who stutter were less likely than White children who stutter to have many worries, to be unhappy/depressed, and less likely to have difficulties with emotions and concentration. Hispanic children who stutter were less likely than White children who stutter to have many worries, to be unhappy/depressed, and less likely to have difficulties with emotions and concentration. Additionally, differences were observed in measures of behavioral, emotional, and social well-being when within-group comparisons were made, as a function of gender, and when comparisons were made across racial-ethnic groups at different age ranges. Conclusions: Evidence from National Health Interview Surveys suggests racial-ethnic differences exist in reports of behavioral, emotional, and social well-being among children who stutter. Future research is needed to clarify specific contributors to the observed differences across racial-ethnic groups and whether differences are primarily associated with race-ethnicity, the presence of stuttering, or both.